Error Analysis of Senior High School Student's Problem Solving Ability on Three Variables Linear Equation System - Kasali, Bagas; Yuliani, Anik; Nurfauziah, Puji ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2023)
Mathematics is a lesson regarded regularly, logically, tiered from the easiest to the most complicated. Mastery and students' understanding of a material can be seen from student mathematical abilities. Analyze the student's error in completing the problem can know the students master a matter or not. This research has a goal to describe and analyze the student's error in completing the line of the linear equation system of three variables. The type of research using descriptive qualitative with the subject of research is a student of X SMAN 1 Pangalengan class. The sample for obtaining data is 6 students who represent high-level, high and low students who are classified from the average results of the test of the linear equivalent system of three variables. The data to be generated are the result of a description test. From the data can be generated by student difficulty analysis in completing the line of the linear equation system of three variables. The slaughter faced by students in the form of errors on conceptual, proseudral and technical. Meanwhile, the lack of understanding the concept of linear equation systems of three variables makes the error of the misman that occur going so that the factors cause the difficulty in the material.